Simultaneously Content Analysis of Sulfadoxine and Pyrimethamine in Tablet Dosage Form by Spectrophotometry Ultraviolet with Dual Wavelenght Method - Muhammad, Andry; Effendy, De lux; Muchlisyam, Putra (Asian Journal of Pharmaceutical Research and Development, 2019)
Aim: method development results from this study are expected to be one of the methods that can be applied by the relevant agencies in determining the simultaneous levels of sulfadoxine and pyrimethamine in tablet dosage form. Pyrimethamine - Sulfadoxine (PS) is an anti-malarial drug combination sulfonamide group / sulfone with nature skizontosida diaminopirimidine network, these drugs are very practical because it can be given in a single dose, and however, this combination provides a new challenge for the pharmaceutical industry in connection with the development of new analytical methods in the determination of levels. Methods: The study was carried out experimentally by spectrophotometric method is the method of multiple wavelengths and then tested for validity based validation parameters, namely linearity, accuracy, precision, LOD and LOQ and intraday and inter day. Then, the method is tested on dosage tablets containing pyrimethamine and sulfadoxine that are on the market. Results: The results showed that the application of the method of multiple wavelengths at a concentration carried out at λ 284.8 nm and 258.8 nm to pyrimethamine and at λ 274.2 nm and 291.6 nm to sulfadoxine. Research results successfully applied the method dual wavelength which is successfully applied to determining the concentration of pyrimethamine and sulfadoxine simultaneously in a tablet.